2009
DOI: 10.1007/s00436-009-1567-x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of two myxosporean species, Myxobolus hakyi sp. n. and Hoferellus pulvinatus sp. n., in Pangasianodon hypophthalmus fry imported from Thailand to Europe as ornamental fish

Abstract: Fingerlings of the sutchi catfish Pangasianodon hypophthalmus, a favorite food fish in South Asia, is regularly imported by European fish traders and sold in pet fish shops. In shipments from Thailand, a skin and a kidney infection of this fish caused by myxosporean parasites was found both in Hungary and Russia. In the skin of the fish, small millet-sized nodules containing great numbers of a Myxobolus species were found, while in the renal glomeruli, spores and sporogonic stages of a Hoferellus species devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
1
13
0
2
Order By: Relevance
“…M. kawabatae is different from M. miyairii by the larger spores and longer polar capsules. Besides the above species found in China, M. hakyi, a recently named sutchi catfishinfecting species found in Thailand is also morphologically similar with M. hiyairii (Baska et al 2009). But the larger spore, less turns of polar filament and infection site can differentiate them (Table 2).…”
Section: Discussionmentioning
confidence: 86%
“…M. kawabatae is different from M. miyairii by the larger spores and longer polar capsules. Besides the above species found in China, M. hakyi, a recently named sutchi catfishinfecting species found in Thailand is also morphologically similar with M. hiyairii (Baska et al 2009). But the larger spore, less turns of polar filament and infection site can differentiate them (Table 2).…”
Section: Discussionmentioning
confidence: 86%
“…The morphology of this species is similar to that of M. miyarii (LIU et al, 2016) and M. cunhai (PENIDO, 1927), given the pyriform shape of the spores, which are distinct from the ovoid spores of M. pangasii (MOLNÁR et al, 2006), the elliptical spores of M. hakyi Baska et al (2009) and M. gayerae Molnár et al (2007), and the spherical spores of M. bivacuolatus (NARASIMHAMURTI & KALAVATI, 1986) (Table 1).…”
Section: Discussionmentioning
confidence: 68%
“…A number of other Myxobolus species found in siluriforms have been described based on the analysis of the 18S rDNA gene, including M. myarii, found in the S. asotus by Liu et al (2016). Using this gene, Baska et al (2009) confirmed the presence of M. hakyi in the epidermis of the P. hypophthalmus, while Molnár et al (2006) found M. pangasii infecting its spleen.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations